Olefin Upgrading Catalysis by Nitrogen-based Metal Complexes II State of the art and Perspectives - CAMPORA, Juan.; GIAMBASTIANI, Giuliano; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Olefin Upgrading Catalysis by Nitrogen-based Metal Complexes II: State of the art and Perspectives provides a critical review of the state-of-the-art developments in industrially relevant processes connected to efficient and selective olefin upgrading. Specific attention is devoted to catalysts containing imine- and amine-based ligands. All the chapters in this book have been designed to provide a systematic account of the vast amount of information available for this type of catalyst as well as to highlight the factors that ultimately control the catalyst$1 (Bs performance and productivity. A comprehensive panorama of catalyst precursors is presented, spanning from group 10 ga(B-diimine complexes and iron and cobalt 2,6-bis(imino)pyridine derivatives, to vanadium, chromium, titanium, zirconium and lanthanide complexes supported by nitrogen-containing ligands. The authors of this collective work are currently involved in the development of imine-based catalysts for efficient and selective olefin upgrading and the majority of them have dedicated most of their scientific career to this important field. In writing this book, their major goal is to transfer as many ideas and experiences as possible to the global audience of scientists engaged in this area of research.s
Keywords: Chemistry; Chemistry, Organic; Polymers; Chemistry; Organic Chemistry; Polymer Sciences